Study on Relationship between UCS of Cemented Tailings Backfill and Weight Losses of Hydration Products - Bingwen Wang; Lijing Gao; Tingyong Xiong; Xiangyu Cui; Yanan Li; Kai Lei (Advances in Civil Engineering)
The weight losses of cement-based material samples were often used to characterize the content of their hydration products and explain the strength changes of cement-based materials. However, the quantitative relationship has not been studied between the weight loss of hydration products and strength of cement-based materials. This paper studied the relationship between the strengths of cemented tailings backfills (CTBs) and the weight losses of its hydration products. The CTB samples have been done, especially on different binders, cement-tailing ratios, mass concentrations, and different curing ages. The uniaxial compressive strength (UCS) experiments were used to test the mechanical strength of samples; X-ray diffraction (XRD) experiments were used to test the crystalline phases of hydration products by samples; thermal analyses (thermogravimetric and differential thermogravimetric (TG/DTG)) experiments were used to test the weight losses of hydration products. By means of regression analysis, the relationship model was established between the UCS of CTB and the weight losses of hydration products at different concentrations. The results show that there is a strong linear correlation between the UCS and the weight loss of the hydration product calcium silicate hydrate (C-S-H) for the CTB made of glue powder, while the UCS is related to the weight losses of C-S-H and Ca(OH)2 for the CTB made of ordinary Portland cement. The results acquired by this paper provide a scientific basis for studying hydration products by thermal analyses and explaining the strength changes of cement-based materials.